SINGLE-ZIRCON PB EVAPORATION GEOCHRONOLOGY CONSTRAINS BASEMENT-COVER RELATIONSHIPS IN THE LOWER HECLA HOEK COMPLEX OF NORTHERN NY FRIESLAND, SVALBARD - Hellman F.J.; Gee D.G.; Witt-Nilsson P.; Johansson Å. (My University, 1997)
The Hecla Hoek Complex, a ∼ 18-km-thick succession in the Svalbard Caledonian Eastern Terrane, has been interpreted to be a more or less continuous volcano-sedimentary sequence. Amphibolite-facies rocks in the lower parts appear to grade conformably up into almost unmetamorphosed Neoproterozoic and Early Paleozoic strata in the middle and upper parts of the succession. However, recent work in the Ny Friesland transpressional orogen has indicated that the lower part of this Hecla Hoek Complex is composed of at least three thrust sheets. Each thrust sheet is made up of Paleoproterozoic ( ∼ 1750 Ma) granites, locally intruded into older metasedimentary rocks, and overlain by younger sedimentary cover, mainly composed of psammites and quartzites, locally with conglomerates.
Keywords: Paleoproterozoic; Neoproterozoic; Paleozoic; Докембрий::Протерозой::Неопротерозойская; Precambrian::Proterozoic::Paleoproterozoic; Paleozoic; Precambrian::Proterozoic::Neoproterozoic; Палеозой; Докембрий::Протерозой::Палеопротерозойская